1987
DOI: 10.1161/01.str.18.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in the Lehigh Valley: seasonal variation in incidence rates.

Abstract: We investigated the seasonal pattern of stroke using the Lehigh Valley Stroke Register. This register includes all patients hospitalized with stroke or transient ischemk attack (TIA) from among the 600,000 Lehigh Valley residents. Meterological data were obtained from the National Oceanic and Atmospheric Administration. The study, which uses 18 months of data, included 1,944 cases. Using single harmonic regression analysis, the seasonal pattern of TIA and infarction, but not hemorrhage, fit a sine-cosine wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
3
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 26 publications
7
57
3
3
Order By: Relevance
“…An earlier study from Japan reported that diurnal temperature change may affect daily blood pressure or autonomic nervous system balance, and, if a considerable diurnal temperature change induces considerable hemodynamic change, it may trigger cerebral stroke. 31 In addition, some studies reported stronger seasonality in stroke in older age groups than in younger ones, 10,11,32,33 as seen in our study. We found a September preponderance in the monthly incidence of AS and IS.…”
Section: 23-25supporting
confidence: 83%
See 2 more Smart Citations
“…An earlier study from Japan reported that diurnal temperature change may affect daily blood pressure or autonomic nervous system balance, and, if a considerable diurnal temperature change induces considerable hemodynamic change, it may trigger cerebral stroke. 31 In addition, some studies reported stronger seasonality in stroke in older age groups than in younger ones, 10,11,32,33 as seen in our study. We found a September preponderance in the monthly incidence of AS and IS.…”
Section: 23-25supporting
confidence: 83%
“…Predictor variables included in these models were mean temperature, diurnal temperature range, humidity, PM 10 , and NO 2 . We scaled RR for temperature at increments of 1°C, for humidity at increments of 5%, and for pollutants at increments of 10 mg/m 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palavras-chave: acidente vascular cerebral, temperatura, risco cardiovascular, sazonal. The correlation between strokes and seasonal variations have been studied in various places [1][2][3][4][5][6][7][8] . Some studies around the world have reported an increase of incidence, mortality, and stroke hospitalization during the coldest months of winter.…”
Section: Introductionmentioning
confidence: 99%
“…For example; although some studies mentioned that the incidence and/or mortality of stroke were highest in winter through colder months (17,18), several reported that ischemic stroke incidence peaks in winter -spring months (19). Some authors also reported that improvement of in home heating might cause decline in stroke incidence (20).…”
Section: Discussionmentioning
confidence: 99%